Hive products effect against fermentativ spoilage yeasts - Rogão, Mónica (2012)
Hive products have recently being in the centre of the international scientific community attention, due to its biological properties.Honey is a sweet aliment produced by honey bees and derived from the nectar of flowers. Propolis is prepared by bees througt the collection of resins from trees and flowers. Bee pollen is the male seed of flowers that is collected by honey bees and mixed with bee secretions. The antimicrobial activity of hive products has been studied namely using pathogenic yeasts, regarding their use on traditional medicine. On the other hand, in literature are not reported studies concerning theis bioactivity against fermentative spoilage yeast, however its significance in food spoilage is increasing, essentially due the new food products development. The main objctive of this study was evaluated the effect of three hive products (honey, propolis and pollen - collected in the Northeast of Portugal) against the fermentative spoilge yeast. For this purpose was used fermentative spoilage yeast-Zygosaccharomyces bailli isolated from wine, Zygosaccharomyces rouxii and Zygosaccharomyces melli isolatrd from honey, and Saccharomyces cerevisiae was used as control. Broth diluition was performed in order to evaluted the antifungal activity of these products. The impact of the different hive products on the survival of fermentative spoilage yeasts was analyzed by calculating the percentge of each product, necessary to reduce 50% of the population (IC50). The results show that all hive products have antifungal properties, however the Ic50 values depends of the strain and hive products. In conclusion, the obtained data are promising for the food industry, since these products could be used to increase shelf-life of food products.